2010
DOI: 10.1159/000322336
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Activating Factor Receptor Mediates Oxidized Low Density Lipoprotein-Induced Migration of Bone Marrow-Derived Mesenchymal Stem Cells

Abstract: Background: Oxidized low density lipoprotein (oxLDL) is involved in the development of vascular diseases. Platelet-activating factor (PAF; 1-O-alkyl-2-acetyl-sn-glyero-3-phosphorylcholine) is a key component of oxLDL. Methods: In the present study, we evaluate whether oxLDL can regulate migration of human bone-marrow derived stem cells (hBMSCs) and characterize the role of PAF in the oxLDL-induced migration. Results and Conclusions: oxLDL stimulated chemotaxis of hBMSCs in vitro. Treatment of the cells with BN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…32 Recent evidence has shown that KLF4 expression can be induced by several factors, including PDGF-BB, POVPC, platelet-activating factor and all-trans retinoic acid in vascular smooth muscle cells and human bone marrow-derived mesenchymal stem cells. 18, 19, 22, 33, 34 POVPC has been reported to induce migration and phenotypic switching of vascular smooth muscle cells through a KLF4-dependent mechanism. 17 In the current study, we demonstrated that LPA treatment resulted in increased expression of KLF4, and siRNA- or shRNA-mediated silencing of KLF4 showed abrogation of LPA-stimulated cell migration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Recent evidence has shown that KLF4 expression can be induced by several factors, including PDGF-BB, POVPC, platelet-activating factor and all-trans retinoic acid in vascular smooth muscle cells and human bone marrow-derived mesenchymal stem cells. 18, 19, 22, 33, 34 POVPC has been reported to induce migration and phenotypic switching of vascular smooth muscle cells through a KLF4-dependent mechanism. 17 In the current study, we demonstrated that LPA treatment resulted in increased expression of KLF4, and siRNA- or shRNA-mediated silencing of KLF4 showed abrogation of LPA-stimulated cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of evidence suggests that KLF4 has a key role in chemotactic migration of several cell types, including mesenchymal stem cells, smooth muscle cells and cancer cells: 17, 18, 19 oxidized phospholipids have been reported to induce migration of vascular smooth muscle through a KLF4-dependent mechanism. 17 We have previously demonstrated that platelet-activating factor or an oxidized phosphatidylcholine POVPC (1-palmitoyl-2-oxovaleroyl- sn -glycero-3-phosphorylcholine) stimulated migration of human bone marrow-derived mesenchymal stem cells by inducing expression levels of KLF4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs co-cultured with mature endothelial cells (ECs) have the ability to undergo milieu-dependent differentiation toward ECs [27]. Migrated MSCs from bone marrow may play a key role in the development of atherogenesis in response to ox-LDL, which could induce MSCs derived smooth muscle like cells to differentiate into foam cells [28,29]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that PAF-R may introduce ox-LDL induced MSC migration [28]. Ox-LDL contains platelet activating factor (PAF) and PAF-like phospholipids [51].…”
Section: Introductionmentioning
confidence: 99%